2020
DOI: 10.1021/acs.chemrestox.0c00076
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Metabolism of Brominated Flame Retardant β-1,2-Dibromo-4-(1,2-dibromoethyl)cyclohexane in Human Microsomal P450 Enzymes: Insights from Computational Studies

Abstract: The emerging brominated flame retardant, 1,2-dibromo-4-(1,2-dibromoethyl)­cyclohexane (TBECH), has recently attracted strong interest due to its extensive detection in the environment and potential toxicological effects on humans. Previous in vitro experiments have shown that the technical mixture of TBECH and the pure β-isomer (β-TBECH) can be metabolized by cytochrome P450 enzymes (CYPs) into multiple metabolites, but the specific CYP isoforms involved in TBECH metabolism and the relevant metabolic regiosele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…We have summarized some relevant calculation results in Table . The energy barriers of the H-abstraction from phenolic hydroxyl are usually quite low, less than 5 kcal/mol , while those from C–H are larger than 13 kcal/mol. According to our calculations, the energy barriers of H1-abstraction catalyzed by DHP B are 9.1 and 8.7 kcal/mol at doublet and quartet states, respectively, which are slightly higher than those of other P450 enzymes. By comparing the structures of reactants with those in other P450s, we found that in the optimized structures of 2 R and 4 R, His55 forms a strong hydrogen bond with the OH group of the substrate.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…We have summarized some relevant calculation results in Table . The energy barriers of the H-abstraction from phenolic hydroxyl are usually quite low, less than 5 kcal/mol , while those from C–H are larger than 13 kcal/mol. According to our calculations, the energy barriers of H1-abstraction catalyzed by DHP B are 9.1 and 8.7 kcal/mol at doublet and quartet states, respectively, which are slightly higher than those of other P450 enzymes. By comparing the structures of reactants with those in other P450s, we found that in the optimized structures of 2 R and 4 R, His55 forms a strong hydrogen bond with the OH group of the substrate.…”
Section: Resultsmentioning
confidence: 58%
“…Our calculation results showed that it is the electron transfer that makes the proton transfer to be quite easy. 69 13.6/16.7 0.9/0.9 TPHP 70 1.3(doublet) triclosan 54 2.5/3.2 BPA 71 0.3/0.3 griseophenone B 72 3.4/2.9 TBECH 73 17.7/18.5 dieldrin 74 14.2/16.3 (R)-2-methylbutyrate 75 19.6/20.9 After H1-proton transfer, there are two reaction pathways starting from IM1b, as shown in Scheme 5. One is the electrophilic addition of FeO to the substrate radical as suggested in the previous study.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the past two decades, molecular modeling techniques, such as molecular dynamics (MD) simulations and quantum chemical calculations, have been extensively used to shed light on the binding and metabolism of xenobiotics in various biomacromolecules including CYPs [38][39][40][41][42][43]. In this work, five OPFRs detected widely in the environment, including TDCIPP, tris(1-chloro-2-propyl) phosphate (TCIPP), tris(2-chloroethyl) phosphate (TCEP), triethyl phosphate (TEP), and EHDPHP (Figure S1 in the Supplementary Materials), were employed to investigate the reaction mechanism leading to their diester metabolites through the density functional theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 99%